KARAKTERISTIK KARKAS DAN DAGING BANDIKUT (Echymipera kalubu) - Warsono, Irba Unggul (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2010)
The research was conducted to study the carcass and meat characteristics of the spiny bandicoots (Echymipera kalubu) using explorative method. In the experiment, twenty bandicoots were used and measured on meat and carcass characteristics. The results showed that the White breast bandicoots had higher meat hind leg and lighter meat fore leg compared with which the Red breast bandicoots. Meat and carcass characteristics of male and female bandicoots were dressing percentage (70.48 and 65.13), pH (5.78 and 5.66), tenderness (1.03 and 1.07 kg/cm2), cooking loss (33.62 and 34.47 %) and water holding capacity (37.14 and 35.98 % mgH2O).